Efficiency of buquinolate in growing-finishing swine diets - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A feeding trial utilizing one-hundred and twelve growing-finishing Duroc pigs was conducted to evaluate the effect of buquinolate (0, 30, 60, or 90g/t) in their diets on growth, efficiency, and carcass quality. Pigs fed 30g/t or 90g/t buquinolate gained four percent faster than did control pigs; however, the feed required per pound of gain was the same. Carcass quality was similar for all treatment groups.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Buquinolate; Growing-finishing pigs; Carcass quality